2007
DOI: 10.1111/j.1440-1746.2007.05032.x
|View full text |Cite
|
Sign up to set email alerts
|

Directly observed therapy for the treatment of hepatitis C virus infection in current and former injection drug users

Abstract: Treatment of HCV in current and former IDU within a multidisciplinary DOT program can be successfully undertaken, resulting in SVR similar to those in randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 35 publications
9
64
1
Order By: Relevance
“…The RCT demonstrated that patients who underwent DOT had greater success in achieving an SVR 63. DOT has a dual advantage of allowing assessment of adherence and an intervention that supports patients at risk of low adherence 64,65…”
Section: Interventions To Support Adherencementioning
confidence: 99%
“…The RCT demonstrated that patients who underwent DOT had greater success in achieving an SVR 63. DOT has a dual advantage of allowing assessment of adherence and an intervention that supports patients at risk of low adherence 64,65…”
Section: Interventions To Support Adherencementioning
confidence: 99%
“…8 In view of the complexity of the therapeutic regime, the side effects and concerns that those who continue to inject may re-infect themselves, many authorities have advised that active injectors should not receive therapy; for example, the 2001 UK guidelines recommend that 'current intravenous drug users should not be treated'. 9 Attitudes to therapy in injectors have evolved 10 14 In these studies, patients with circumstances that were thought to reduce compliance (such as lack of a fixed abode) were excluded and thus compliance in socially challenged injecting drug users has not been assessed. This has led to diverse guidelines for the management of active injectors with hepatitis C 15 and it remains unclear who is likely to benefit from anti-viral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is much work that has been done with regard to HIV prevention among IDUs, we still do not know how to successfully prevent HCV infection in this group (Mateu-Gelabert et al, 2007). HCV treatment programs for intravenous drug users have not been included as part of the efforts to reduce the impact of the HIV epidemic (Grebely et al, 2007). Whether as part of a combined HIV/HCV prevention program or a program specifically tailored to HCV alone, much work remains to be done, particularly in the Hispanic/Latino population.…”
Section: Hcv Prevention Studiesmentioning
confidence: 99%